ЛИРИКАЛЫҚ ДҮРКИНЛЕРДИҢ ТЕОРИЯЛЫҚ ТИЙКАРЛАРЫ - Оразымбетова, М.К. (FAN va JAMIYAT, 2017)
The article is devoted to the theoretical basis of lyrical cycles of poems. The author of the article analyses the cycles of poems of the famous Karakalpak poets T.Matmuratov, Sh.Seitov, K.Karimov, K.Rakhmanov, I.Yusupov, Kh.Aiymbetov and others, and the practical implementation of cycles of the famous Russian poets-classics A.S.Pushkin, M.Y.Lermontov and S.Esenin in Karakalpak poetry. The cycles of poems have been studied on the basis of typological comparison.